Effect of cutting length of whole- crop corn silage on quality and rumen fermentation in goats - Khaing, Khin Thida (2015)
Shortage and fluctuating quality of forage in developing countries are the major constraints to the development of ruminant production sector including Malaysia. To overcome these problems, the feeding of ruminants with conserved forages is an important feeding strategy to ensure the success of ruminant production. The use of whole-crop corn as a silage has drawn much attention nowadays. Many factors including forage maturity, particle length, packing density and types of storage could affect the quality of silage. Among these factors, cutting length can be considered as an important element that contributes to the silage quality. Thus, the objectives of this study were to determine suitable cutting length of whole-crop corn for ensiling process and its aerobic stability, and to see if the inclusion of corn silage to Napier grass in ruminant diets at different level had given more nutrients utilization and rumen fermentation. The whole-crop of Suwan corn was harvested at the 1/3 milk line stage of maturity and was cut into different cutting length; 2 cm, 4 cm and 6 cm before inserted into the 1 L air tight glass containers. The bacterial densities consist of total viable bacteria (TVB) and lactic acid bacteria population (LAB), fermentation characteristics and chemical composition were observed weekly starting from week 1 until week 5 of ensiling period. Samples of corn silage at week 5 were used to observe in vitro gas production and in situ ruminal degradability. The aerobic stability of the silage was determined immediately at day 0, day 1 and day 2 after 5 weeks of ensilaged samples were opened. The aerobic stability measuring parameters were microbial analyses that involved TVB, LAB, yeasts and moulds, fermentation characteristics, and chemical analysis. Based on the data reported in experiments 1 and 2, the 2 cm cutting length of whole-crop corn silage was used for the feeding trial that was conducted on 15 male Boer cross goats around six months old of approximately 18.54 ± 1.83 kg of body weights. The goats were assigned into five treatment groups consisted of different proportions of Napier grass (G) and whole plant corn silage (CS) – G/CS; T1:100/0; T2:75/25; T3:50/50; T4:25/75 and T5:0/100 respectively. The measurement parameters were feed intake, growth performance, digestibility, rumen fermentation characteristics and rumen microbial populations. Results showed that the bacterial densities of TVB and LAB were significantly different (P <0.05) among the treatment groups at the ensiling period of week 1 until week 3. The concentration of fermentation acids demonstrated high level of lactic and low level of butyric acid in the 2 cm cutting length of corn silage. The in vitro gas production and the DM, OM and CP disappearance percentage of short cutting length were significantly higher (P<0.05) than long cutting lengths. The results of aerobic stability measurements showed that the changes in microbial populations observed during exposure to air, but no significant result was observed among the cutting lengths of whole-crop corn silage. The concentrations of fermentative acids and chemical composition of all cutting length were reduced throughout the period of aerobic exposure. An increase of corn silage to Napier grass proportion resulted in an increase in feed intake and growth performance in goats. The highest nutrient digestibility was observed in T5 and T3 diets. The highest proportion of propionic and lowest proportion of acetic acid was observed in T5 diet. The numbers of total bacteria populations were not significantly different among the treatment diets. However, the lowest population of protozoa and methanogen were detected in the rumen of goats fed T5 diet. Based on the results obtained in this study, it can be concluded that short cutting length (2 cm) showed good fermentation characteristics than long cutting length of whole-crop corn silage. The cutting length had no effect on aerobic stability, and all of the treatments silages spoiled after 1 day of aerobic exposure. Apart from that, high proportion of corn silage to grass diets resulted in increase in feed intake and growth performance of goats. Rumen fermentation profiles were significantly different among the treatment groups. Although total bacteria populations were not significantly different among the treatment diets, the populations of methanogen and protozoa were lowest in goat fed with T5 diet.